Blocking the angiopoietin-2-dependent integrin β-1 signaling axis abrogates small cell lung cancer invasion and metastasis - Meder, Lydia; Orschel, Charlotte Isabelle; Otto, Christoph Julius; Koker, Mirjam; Brägelmann, Johannes; Ercanoglu, Meryem S.; Dähling, Sabrina; Compes, Anik; Selenz, Carolin; Nill, Marieke; Dietlein, Felix; Florin, Alexandra; et al. (JCI Insight, 2024)
Small cell lung cancer (SCLC) is the most aggressive lung cancer entity with an extremely limited therapeutic outcome. Most patients are diagnosed at an extensive stage. However, the molecular mechanisms driving SCLC invasion and metastasis remain largely elusive. We used an autochthonous SCLC mouse model and matched samples from patients with primary and metastatic SCLC to investigate the molecular characteristics of tumor metastasis. We demonstrate that tumor cell invasion and liver metastasis in SCLC are triggered by an Angiopoietin-2 (ANG-2)/Integrin β-1-dependent pathway in tumor cells, mediated by focal adhesion kinase/Src kinase signaling. Strikingly, CRISPR-Cas9 KO of Integrin β-1 or blocking Integrin β-1 signaling by an anti-ANG-2 treatment abrogates liver metastasis formation in vivo. Interestingly, analysis of a unique collection of matched samples from patients with primary and metastatic SCLC confirmed a strong increase of Integrin β-1 in liver metastasis in comparison with the primary tumor. We further show that ANG-2 blockade combined with PD-1-targeted by anti-PD-1 treatment displays synergistic treatment effects in SCLC. Together, our data demonstrate a fundamental role of ANG-2/Integrin β-1 signaling in SCLC cells for tumor cell invasion and liver metastasis and provide a potentially new effective treatment strategy for patients with SCLC.
CRIS-Team Scopus Importer:2024-05-31

Combined VEGF and PD-L1 blockade displays synergistic treatment effects in an autochthonous mouse model of small cell lung cancer - Meder, Lydia; Schuldt, Philipp; Thelen, Martin; Schmitt, Anna; Dietlein, Felix; Klein, Sebastian; Borchmann, Sven; Wennhold, Kerstin; Vlasic, Ignacija; Oberbeck, Sebastian; Riedel, Richard; Florin, Alexandra; et al. (Cancer Research, 2018)
Small cell lung cancer (SCLC) represents the most aggressive pulmonary neoplasm and is often diagnosed at late stage with limited survival, despite combined chemotherapies. We show in an autochthonous mouse model of SCLC that combined anti-VEGF/anti-PD-L1-targeted therapy synergistically improves treatment outcome compared with anti-PD-L1 and anti-VEGF monotherapy. Mice treated with anti-PD-L1 alone relapsed after 3 weeks and were associated with a tumorassociated PD-1/TIM-3 double-positive exhausted T-cell phenotype. This exhausted T-cell phenotype upon PD-L1 blockade was abrogated by the addition of anti-VEGF-targeted treatment. We confirmed a similar TIM-3-positive T-cell phenotype in peripheral blood mononuclear cells of patients with SCLC with adaptive resistance to anti-PD-1 treatment. Mechanistically, we show that VEGFA enhances coexpression of the inhibitory receptor TIM-3 on T cells, indicating an immunosuppressive function of VEGF in patients with SCLC during anti-PD-1-targeted treatment. Our data strongly suggest that a combination of anti-VEGF and anti-PD-L1 therapies can be an effective treatment strategy in patients with SCLC.
CRIS-Team Scopus Importer:2023-03-21

Deregulation and epigenetic modification of BCL2-family genes cause resistance to venetoclax in hematologic malignancies - Thomalla, D.; Beckmann, Laura; Grimm, Christina; Oliverio, Matteo; Meder, L.; Herling, C. D.; Nieper, P.; Feldmann, T.; Merkel, O.; Lorsy, E.; Guerreiro, A. Da Palma; Von Jan, J.; et al. (Blood, 2022)
The BCL2 inhibitor venetoclax has been approved to treat different hematological malignancies. Because there is no common genetic alteration causing resistance to venetoclax in chronic lymphocytic leukemia (CLL) and B-cell lymphoma, we asked if epigenetic events might be involved in venetoclax resistance. Therefore, we employed whole-exome sequencing, methylated DNA immunoprecipitation sequencing, and genome-wide clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 screening to investigate venetoclax resistance in aggressive lymphoma and high-risk CLL patients. We identified a regulatory CpG island within the PUMA promoter that is methylated upon venetoclax treatment, mediating PUMA downregulation on transcript and protein level. PUMA expression and sensitivity toward venetoclax can be restored by inhibition of methyltransferases. We can demonstrate that loss of PUMA results in metabolic reprogramming with higher oxidative phosphorylation and adenosine triphosphate production, resembling the metabolic phenotype that is seen upon venetoclax resistance. Although PUMA loss is specific for acquired venetoclax resistance but not for acquired MCL1 resistance and is not seen in CLL patients after chemotherapy-resistance, BAX is essential for sensitivity toward both venetoclax and MCL1 inhibition. As we found loss of BAX in Richter's syndrome patients after venetoclax failure, we defined BAX-mediated apoptosis to be critical for drug resistance but not for disease progression of CLL into aggressive diffuse large B-cell lymphoma in vivo. A compound screen revealed TRAIL-mediated apoptosis as a target to overcome BAX deficiency. Furthermore, antibody or CAR T cells eliminated venetoclax resistant lymphoma cells, paving a clinically applicable way to overcome venetoclax resistance.
CRIS-Team Scopus Importer:2023-03-21

Differential protein stability and ALK inhibitor sensitivity of EML4-ALK fusion variants - Heuckmann, Johannes M.; Balke-Want, Hyatt; Malchers, Florian; Peifer, Martin; Sos, Martin L.; Koker, Mirjam; Meder, Lydia; Lovly, Christine M.; Heukamp, Lukas C.; Pao, William; Kueppers, Ralf; Thomas, Roman K. (Clinical Cancer Research, 2012)
Purpose: ALK rearrangement-positive lung cancers can be effectively treated with ALK inhibitors. However, the magnitude and duration of response is heterogeneous. In addition, acquired resistance limits the efficacy of ALK inhibitors, with most upfront resistance mechanisms being unknown. Experimental Design: By making use of the Ba/F3 cell line model, we analyzed the cytotoxic efficacy of ALK kinase inhibitors as a function of different EML4-ALK fusion variants v1, v2, v3a, and v3b as well as of three artificially designed EML4-ALK deletion constructs and the ALK fusion genes KIF5b-ALK and NPM1-ALK. In addition, the intracellular localization, the sensitivity to HSP90 inhibition and the protein stability of ALK fusion proteins were studied. Results: Different ALK fusion genes and EML4-ALK variants exhibited differential sensitivity to the structurally diverse ALK kinase inhibitors crizotinib and TAE684. In addition, differential sensitivity correlated with differences in protein stability in EML4-ALK-expressing cells. Furthermore, the sensitivity to HSP90 inhibition also varied depending on the ALK fusion partner but differed from ALK inhibitor sensitivity patterns. Finally, combining inhibitors of ALK and HSP90 resulted in synergistic cytotoxicity. Conclusions: Our results might explain some of the heterogeneous responses of ALK-positive tumors to ALK kinase inhibition observed in the clinic. Thus, targeted therapy of ALK-positive lung cancer should take into account the precise ALK genotype. Furthermore, combining ALK and HSP90 inhibitors might enhance tumor shrinkage in EML4-ALK-driven tumors. ©2012 AACR.
CRIS-Team Scopus Importer:2023-03-21

EGFR Inhibition Strongly Modulates the Tumour Immune Microenvironment in EGFR-Driven Non-Small-Cell Lung Cancer - Selenz, Carolin; Compes, Anik; Nill, Marieke; Borchmann, Sven; Odenthal, Margarete; Florin, Alexandra; Braegelmann, Johannes; Buettner, Reinhard; Meder, Lydia; Ullrich, Roland T. (Cancers, 2022)
EGFR-driven non-small-cell lung cancer (NSCLC) patients are currently treated with TKIs targeting EGFR, such as erlotinib or osimertinib. Despite a promising initial response to TKI treatment, most patients gain resistance to oncogene-targeted therapy, and tumours progress. With the development of inhibitors against immune checkpoints, such as PD-1, that mediate an immunosuppressive microenvironment, immunotherapy approaches attempt to restore a proinflammatory immune response in tumours. However, this strategy has shown only limited benefits in EGFR-driven NSCLC. Approaches combining EGFR inhibition with immunotherapy to stimulate the immune response and overcome resistance to therapy have been limited due to insufficient understanding about the effect of EGFR-targeting treatment on the immune cells in the TME. Here, we investigate the impact of EGFR inhibition by erlotinib on the TME and its effect on the antitumour response of the immune cell infiltrate. For this purpose, we used a transgenic conditional mouse model to study the immunological profile in EGFR-driven NSCLC tumours. We found that EGFR inhibition mediated a higher infiltration of immune cells and increased local proliferation of T-cells in the tumours. Moreover, inhibiting EGFR signalling led to increased activation of immune cells in the TME. Most strikingly, combined simultaneous blockade of EGFR and anti-PD-1 (aPD-1) enhanced tumour treatment response in a transgenic mouse model of EGFR-driven NSCLC. Thus, our findings show that EGFR inhibition promotes an active and proinflammatory immune cell infiltrate in the TME while improving response to immune checkpoint inhibitors in EGFR-driven NSCLC.
CRIS-Team Scopus Importer:2023-03-21
Keywords: anti-PD-1; EGFR; erlotinib; immune cell infiltrate; immune checkpoint blockade; immune response; NSCLC; tumour microenvironment; tyrosine kinase inhibitors

Elucidating alternative pathways triggering small cell lung carcinoma tumor biology - Meder, Lydia; Buettner, Reinhard (TRANSLATIONAL CANCER RESEARCH, 2016)
CRIS-Team Scopus Importer:2023-03-21

Erratum: Tumor VEGF:VEGFR2 autocrine feed-forward loop triggers angiogenesis in lung cancer (Journal of Clinical Investigation (2013) 123, 7 (3183) DOI:10.1172/JCI65385) - Chatterjee, Sampurna; Heukamp, Lukas C.; Siobal, Maike; Schoettle, Jakob; Wieczorek, Caroline; Peifer, Martin; Frasca, Davide; Koker, Mirjam; Koenig, Katharina; Meder, Lydia; Rauh, Daniel; Buettner, Reinhard; et al. (Journal of Clinical Investigation, 2013)
CRIS-Team Scopus Importer:2023-03-21

Hepatic FTO is dispensable for the regulation of metabolism but counteracts HCC development in vivo - Mittenbuhler, Melanie J.; Saedler, Katarzyna; Nolte, Hendrik; Kern, Lara; Zhou, Jun; Qian, Shu-Bing; Meder, Lydia; Ullrich, Roland T.; Bruening, Jens C.; Wunderlich, F. Thomas (Molecular Metabolism, 2020)
Objective: Single-nucleotide polymorphisms in the FTO gene encoding an m6Am and an m6A demethylase are associated with obesity. Moreover, recent studies have linked a dysregulation of m6A modifications and its machinery, including FTO, to the development of several forms of cancers. However, the functional role of hepatic FTO in metabolism and the development and progression of hepatocellular carcinoma (HCC), a proteotypic obesity-associated cancer, remains unclear. Thus, we aimed to reveal the role of hepatic FTO in metabolism and in the initiation and progression of HCC in vivo. Methods: We generated mice with hepatic FTO deficiency (FTOL−KO). The effect of hepatic FTO on metabolism was investigated by extensive metabolic phenotyping. To determine the impact of hepatic FTO on HCC development, FTOL−KO and Ctrl mice were subjected to long-term diethylnitrosamine (DEN)-induced HCC-development and the tumor initiation phase was examined via a short-term DEN protocol. Results: In long-term DEN experiments, FTOL−KO mice exhibit increased HCC burden compared to Ctrl mice. In the tumor initiation phase, Ctrl mice display a dynamic regulation of FTO upon induction of liver damage, while this response is abrogated in FTO-deficient mice. Proteomic analyses revealed that liver damage-induced increases in FTO expression reduce CUL4A protein abundance. Functionally, simultaneous knockdown of Cul4a reverses the increased hepatocyte proliferation observed upon loss of FTO. Conclusion: Collectively, our study demonstrates that hepatic FTO is dispensable for the control of energy homeostasis and glucose metabolism. However, we show a protective function of FTO in liver carcinogenesis and suggest the FTO-dependent dynamic mRNA demethylation of Cul4a in the initiation of HCC development contributes to this effect.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Cul4a; FTO; Hepatocellular carcinoma; m

Heterogeneous mechanisms of primary and acquired resistance to third-generation EGFR inhibitors - Ortiz-Cuaran, Sandra; Scheffler, Matthias; Plenker, Dennis; Dahmen, Ilona; Scheel, Andreas H.; Fernandez-Cuesta, Lynnette; Meder, Lydia; Lovly, Christine M.; Persigehl, Thorsten; Merkelbach-Bruse, Sabine; Bos, Marc; Michels, Sebastian; et al. (Clinical Cancer Research, 2016)
Purpose: To identify novel mechanisms of resistance to thirdgeneration EGFR inhibitors in patients with lung adenocarcinoma that progressed under therapy with either AZD9291 or rociletinib (CO-1686). Experimental Design: We analyzed tumor biopsies from seven patients obtained before, during, and/or after treatment with AZD9291 or rociletinib (CO-1686). Targeted sequencing and FISH analyses were performed, and the relevance of candidate genes was functionally assessed in in vitro models. Results: We found recurrent amplification of either MET or ERBB2 in tumors that were resistant or developed resistance to third-generation EGFR inhibitors and show that ERBB2 and MET activation can confer resistance to these compounds. Furthermore, we identified a KRASG12S mutation in a patient with acquired resistance to AZD9291 as a potential driver of acquired resistance. Finally, we show that dual inhibition of EGFR/MEK might be a viable strategy to overcome resistance in EGFR-mutant cells expressing mutant KRAS. Conclusions: Our data suggest that heterogeneous mechanisms of resistance can drive primary and acquired resistance to third-generation EGFR inhibitors and provide a rationale for potential combination strategies. Clin Cancer Res; 22(19); 4837-47.
CRIS-Team Scopus Importer:2023-03-21

Implementation of amplicon parallel sequencing leads to improvement of diagnosis and therapy of lung cancer patients - Koenig, Katharina; Peifer, Martin; Fassunke, Jana; Ihle, Michaela A.; Kuenstlinger, Helen; Heydt, Carina; Stamm, Katrin; Ueckeroth, Frank; Vollbrecht, Claudia; Bos, Marc; Gardizi, Masyar; Scheffler, Matthias; et al. (Journal of Thoracic Oncology, 2015)
Introduction: The Network Genomic Medicine Lung Cancer was set up to rapidly translate scientific advances into early clinical trials of targeted therapies in lung cancer performing molecular analyses of more than 3500 patients annually. Because sequential analysis of the relevant driver mutations on fixated samples is challenging in terms of workload, tissue availability, and cost, we established multiplex parallel sequencing in routine diagnostics. The aim was to analyze all therapeutically relevant mutations in lung cancer samples in a high-throughput fashion while significantly reducing turnaround time and amount of input DNA compared with conventional dideoxy sequencing of single polymerase chain reaction amplicons. Methods: In this study, we demonstrate the feasibility of a 102 amplicon multiplex polymerase chain reaction followed by sequencing on an Illumina sequencer on formalin-fixed paraffin-embedded tissue in routine diagnostics. Analysis of a validation cohort of 180 samples showed this approach to require significantly less input material and to be more reliable, robust, and cost-effective than conventional dideoxy sequencing. Subsequently, 2657 lung cancer patients were analyzed. Results: We observed that comprehensive biomarker testing provided novel information in addition to histological diagnosis and clinical staging. In 2657 consecutively analyzed lung cancer samples, we identified driver mutations at the expected prevalence. Furthermore we found potentially targetable DDR2 mutations at a frequency of 3% in both adenocarcinomas and squamous cell carcinomas. Conclusion: Overall, our data demonstrate the utility of systematic sequencing analysis in a clinical routine setting and highlight the dramatic impact of such an approach on the availability of therapeutic strategies for the targeted treatment of individual cancer patients.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Amplicon; Formalin-fixed; Lung cancer; Next-generation sequencing; Routine diagnostic

Implementing amplicon-based next generation sequencing in the diagnosis of small cell lung carcinoma metastases - Meder, Lydia; Koenig, Katharina; Fassunke, Jana; Ozretic, Luka; Wolf, Juergen; Merkelbach-Bruse, Sabine; Heukamp, Lukas C.; Buettner, Reinhard (Experimental and Molecular Pathology, 2015)
Small cell lung carcinoma (SCLC) is the most aggressive entity of lung cancer. Rapid cancer progression and early formation of systemic metastases drive the deadly outcome of SCLC. Recent advances in identifying oncogenes by cancer whole genome sequencing improved the understanding of SCLC carcinogenesis. However, tumor material is often limited in the clinic. Thus, it is a compulsive issue to improve SCLC diagnostics by combining established immunohistochemistry and next generation sequencing. We implemented amplicon-based next generation deep sequencing in our routine diagnostics pipeline to analyze RB1, TP53, EP300 and CREBBP, frequently mutated in SCLC. Thereby, our pipeline combined routine SCLC histology and identification of somatic mutations. We comprehensively analyzed fifty randomly collected SCLC metastases isolated from trachea and lymph nodes in comparison to specimens derived from primary SCLC.SCLC lymph node metastases showed enhanced proliferation and frequently a collapsed keratin cytoskeleton compared to SCLC metastases isolated from trachea. We identified characteristic synchronous mutations in RB1 and TP53 and non-synchronous CREBBP and EP300 mutations. Our data showed the benefit of implementing deep sequencing into routine diagnostics. We here identify oncogenic drivers and simultaneously gain further insights into SCLC tumor biology.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Amplicon-based next generation sequencing; Metastasis; P53; Retinoblastoma protein; Routine diagnostics; Small cell lung cancer

Inhibition of Tumor VEGFR2 Induces Serine 897 EphA2-Dependent Tumor Cell Invasion and Metastasis in NSCLC - Volz, Caroline; Breid, Sara; Selenz, Carolin; Zaplatina, Alina; Golfmann, Kristina; Meder, Lydia; Dietlein, Felix; Borchmann, Sven; Chatterjee, Sampurna; Siobal, Maike; Schoettle, Jakob; Florin, Alexandra; et al. (Cell Reports, 2020)
Anti-angiogenic treatment targeting vascular endothelial growth factor (VEGF)-VEGFR2 signaling has shown limited efficacy in lung cancer patients. Here, we demonstrate that inhibition of VEGFR2 in tumor cells, expressed in ∼20% of non-squamous non-small cell lung cancer (NSCLC) patients, leads to a pro-invasive phenotype. Drug-induced inhibition of tumor VEGFR2 interferes with the formation of the EphA2/VEGFR2 heterocomplex, thereby allowing RSK to interact with Serine 897 of EphA2. Inhibition of RSK decreases phosphorylation of Serine 897 EphA2. Selective genetic modeling of Serine 897 of EphA2 or inhibition of EphA2 abrogates the formation of metastases in vivo upon VEGFR2 inhibition. In summary, these findings demonstrate that VEGFR2-targeted therapy conditions VEGFR2-positive NSCLC to Serine 897 EphA2-dependent aggressive tumor growth and metastasis. These data shed light on the molecular mechanisms explaining the limited efficacy of VEGFR2-targeted anti-angiogenic treatment in lung cancer patients.
CRIS-Team Scopus Importer:2023-03-21
Keywords: NSCLC; RSK; S897 EphA2; tumor cell invasion; VEGFR2 inhibition

LIN28B enhanced tumorigenesis in an autochthonous KRASG12V-driven lung carcinoma mouse model - Meder, Lydia; Koenig, Katharina; Dietlein, Felix; Macheleidt, Iris; Florin, Alexandra; Ercanoglu, Meryem S.; Rommerscheidt-Fuss, Ursula; Koker, Mirjam; Schoen, Gisela; Odenthal, Margarete; Klein, Florian; Buettner, Reinhard; et al. (Oncogene, 2018)
LIN28B is a RNA-binding protein regulating predominantly let-7 microRNAs with essential functions in inflammation, wound healing, embryonic stem cells, and cancer. LIN28B expression is associated with tumor initiation, progression, resistance, and poor outcome in several solid cancers, including lung cancer. However, the functional role of LIN28B, especially in non-small cell lung adenocarcinomas, remains elusive. Here, we investigated the effects of LIN28B expression on lung tumorigenesis using LIN28B transgenic overexpression in an autochthonous KRAS G12V -driven mouse model. We found that LIN28B overexpression significantly increased the number of CD44+/CD326+ tumor cells, upregulated VEGF-A and miR-21 and promoted tumor angiogenesis and epithelial-to-mesenchymal transition (EMT) accompanied by enhanced AKT phosphorylation and nuclear translocation of c-MYC. Moreover, LIN28B accelerated tumor initiation and enhanced proliferation which led to a shortened overall survival. In addition, we analyzed lung adenocarcinomas of the Cancer Genome Atlas (TCGA) and found LIN28B expression in 24% of KRAS-mutated cases, which underscore the relevance of our model.
CRIS-Team Scopus Importer:2023-03-21

Loss of the Keratin Cytoskeleton Is Not Sufficient to Induce Epithelial Mesenchymal Transition in a Novel KRAS Driven Sporadic Lung Cancer Mouse Model - Koenig, Katharina; Meder, Lydia; Kroeger, Cornelia; Diehl, Linda; Florin, Alexandra; Rommerscheidt-Fuss, Ursula; Kahl, Philip; Wardelmann, Eva; Magin, Thomas M.; Buettner, Reinhard; Heukamp, Lukas C. (PLoS ONE, 2013)
Epithelial-to-mesenchymal transition (EMT), the phenotypical change of cells from an epithelial to a mesenchymal type, is thought to be a key event in invasion and metastasis of adenocarcinomas. These changes involve loss of keratin expression as well as loss of cell polarity and adhesion. We here aimed to determine whether the loss of keratin expression itself drives increased invasion and metastasis in adenocarcinomas and whether keratin loss leads to the phenotypic changes associated with EMT. Therefore, we employed a recently described murine model in which conditional deletion of the Keratin cluster II by Cre-recombinase leads to the loss of the entire keratinmultiprotein family. These mice were crossed into a newly generated Cre-recombinase inducible KRAS-driven murine lung cancer model to examine the effect of keratin loss on morphology, invasion and metastasis as well as expression of EMT related genes in the resulting tumors. We here clearly show that loss of a functional keratin cytoskeleton did not significantly alter tumor morphology or biology in terms of invasion, metastasis, proliferation or tumor burden and did not lead to induction of EMT. Further, tumor cells did not induce synchronously expression of vimentin, which is often seen in EMT, to compensate for keratin loss. In summary, our data suggest that changes in cell shape and migration that underlie EMT are dependent on changes in signaling pathways that cause secondary changes in keratin expression and organization. Thus, we conclude that loss of the keratin cytoskeleton per se is not sufficient to causally drive EMT in this tumor model. © 2013 König et al.
CRIS-Team Scopus Importer:2023-03-21

MAPK-pathway inhibition mediates inflammatory reprogramming and sensitizes tumors to targeted activation of innate immunity sensor RIG-I - Braegelmann, Johannes; Lorenz, Carina; Borchmann, Sven; Nishii, Kazuya; Wegner, Julia; Meder, Lydia; Ostendorp, Jenny; Ast, David F.; Heimsoeth, Alena; Nakasuka, Takamasa; Hirabae, Atsuko; Okawa, Sachi; et al. (Nature Communications, 2021)
Kinase inhibitors suppress the growth of oncogene driven cancer but also enforce the selection of treatment resistant cells that are thought to promote tumor relapse in patients. Here, we report transcriptomic and functional genomics analyses of cells and tumors within their microenvironment across different genotypes that persist during kinase inhibitor treatment. We uncover a conserved, MAPK/IRF1-mediated inflammatory response in tumors that undergo stemness- and senescence-associated reprogramming. In these tumor cells, activation of the innate immunity sensor RIG-I via its agonist IVT4, triggers an interferon and a pro-apoptotic response that synergize with concomitant kinase inhibition. In humanized lung cancer xenografts and a syngeneic Egfr-driven lung cancer model these effects translate into reduction of exhausted CD8+ T cells and robust tumor shrinkage. Overall, the mechanistic understanding of MAPK/IRF1-mediated intratumoral reprogramming may ultimately prolong the efficacy of targeted drugs in genetically defined cancer patients.
CRIS-Team Scopus Importer:2023-03-21

Notch1 Deficiency Induces Tumor Cell Accumulation Inside the Bronchiolar Lumen and Increases TAZ Expression in an Autochthonous Kras LSL-G12V Driven Lung Cancer Mouse Model - Meder, Lydia; Florin, Alexandra; Ozretic, Luka; Nill, Marieke; Koker, Mirjam; Meemboor, Sonja; Radtke, Freddy; Diehl, Linda; Ullrich, Roland T.; Odenthal, Margarete; Buettner, Reinhard; Heukamp, Lukas C. (Pathology & Oncology Research, 2021)
Purpose: Abrogation of Notch signaling, which is pivotal for lung development and pulmonary epithelial cell fate decisions was shown to be involved in the aggressiveness and the differentiation of lung carcinomas. Additionally, the transcription factors YAP and TAZ which are involved in the Hippo pathway, were recently shown to be tightly linked with Notch signaling and to regulate the cell fate in epidermal stem cells. Thus, we aim to elucidate the effects of conditional Notch1 deficiency on carcinogenesis and TAZ expression in lung cancer. Methods: We investigated the effect of conditional Cre-recombinase mediated Notch1 knock-out on lung cancer cells in vivo using an autochthonous mouse model of lung adenocarcinomas driven by KrasLSL-G12V and comprehensive immunohistochemical analysis. In addition, we analyzed clinical samples and human lung cancer cell lines for TAZ expression and supported our findings by publicly available data from The Cancer Genome Atlas (TCGA). Results: In mice, we found induction of papillary adenocarcinomas and protrusions of tumor cells from the bronchiolar lining upon Notch1 deficiency. Moreover, the mutated Kras driven lung tumors with deleted Notch1 showed increased TAZ expression and focal nuclear translocation which was frequently observed in human pulmonary adenocarcinomas and squamous cell carcinomas of the lung, but not in small cell lung carcinomas. In addition, we used data from TCGA to show that putative inactivating NOTCH1 mutations co-occur with KRAS mutations and genomic amplifications in lung adenocarcinomas. Conclusion: Our in vivo study provides evidence that Notch1 deficiency in mutated Kras driven lung carcinomas contributes to lung carcinogenesis in a subgroup of patients by increasing TAZ expression who might benefit from TAZ signaling blockade.
CRIS-Team Scopus Importer:2023-03-21
Keywords: KRAS; lung cancer; mouse model; NOTCH1; TAZ

NOTCH, ASCL1, p53 and RB alterations define an alternative pathway driving neuroendocrine and small cell lung carcinomas - Meder, Lydia; Koenig, Katharina; Ozretic, Luka; Schultheis, Anne M.; Ueckeroth, Frank; Ade, Carsten P.; Albus, Kerstin; Boehm, Diana; Rommerscheidt-Fuss, Ursula; Florin, Alexandra; Buhl, Theresa; Hartmann, Wolfgang; et al. (International Journal of Cancer, 2016)
Small cell lung cancers (SCLCs) and extrapulmonary small cell cancers (SCCs) are very aggressive tumors arising de novo as primary small cell cancer with characteristic genetic lesions in RB1 and TP53. Based on murine models, neuroendocrine stem cells of the terminal bronchioli have been postulated as the cellular origin of primary SCLC. However, both in lung and many other organs, combined small cell/non-small cell tumors and secondary transitions from non-small cell carcinomas upon cancer therapy to neuroendocrine and small cell tumors occur. We define features of "small cell-ness" based on neuroendocrine markers, characteristic RB1 and TP53 mutations and small cell morphology. Furthermore, here we identify a pathway driving the pathogenesis of secondary SCLC involving inactivating NOTCH mutations, activation of the NOTCH target ASCL1 and canonical WNT-signaling in the context of mutual bi-allelic RB1 and TP53 lesions. Additionaly, we explored ASCL1 dependent RB inactivation by phosphorylation, which is reversible by CDK5 inhibition. We experimentally verify the NOTCH-ASCL1-RB-p53 signaling axis in vitro and validate its activation by genetic alterations in vivo. We analyzed clinical tumor samples including SCLC, SCC and pulmonary large cell neuroendocrine carcinomas and adenocarcinomas using amplicon-based Next Generation Sequencing, immunohistochemistry and fluorescence in situ hybridization. In conclusion, we identified a novel pathway underlying rare secondary SCLC which may drive small cell carcinomas in organs other than lung, as well. What's new? Using next generation sequencing and establishing features of 'small cell-ness', we identified a NOTCH-ASCL1-RB1-TP53 signaling axis driving small cell cancers. In contrast to the previously described bi-allelic RB1/TP53 loss in neuroendocrine stem cells as origin of primary small cell neuroendocrine cancers, the NOTCH-ASCL1 mediated signaling defines an alternative pathway driving secondary small cell neuroendocrine cancers arising from non-small cell cancers. Moreover, we show a preclinical rational for therapeutically testing WNT-inhibitors in small cell cancers.
CRIS-Team Scopus Importer:2023-03-21
Keywords: achaete-scute homolog 1; Lung cancer; neurogenic locus notch homolog; retinoblastoma protein; small cell lung cancer

Notch signaling triggers the tumor heterogeneity of small cell lung cancer - Meder, Lydia; Buettner, Reinhard; Odenthal, Margarete (Journal of Thoracic Disease, 2017)
CRIS-Team Scopus Importer:2023-03-21

Pericentromeric Satellite III transcripts induce etoposide resistance - Kanne, Julian; Hussong, Michelle; Isensee, Joerg; Munoz-Lopez, Alvaro; Wolffgramm, Jan; Hess, Felix; Grimm, Christina; Bessonov, Sergey; Meder, Lydia; Wang, Jie; Reinhardt, H. Christian; Odenthal, Margarete; et al. (Cell Death & Disease, 2021)
Non-coding RNA from pericentromeric satellite repeats are involved in stress-dependent splicing processes, maintenance of heterochromatin, and are required to protect genome stability. Here we show that the long non-coding satellite III RNA (SatIII) generates resistance against the topoisomerase IIa (TOP2A) inhibitor etoposide in lung cancer. Because heat shock conditions (HS) protect cells against the toxicity of etoposide, and SatIII is significantly induced under HS, we hypothesized that the protective effect could be traced back to SatIII. Using genome methylation profiles of patient-derived xenograft mouse models we show that the epigenetic modification of the SatIII DNA locus and the resulting SatIII expression predict chemotherapy resistance. In response to stress, SatIII recruits TOP2A to nuclear stress bodies, which protects TOP2A from a complex formation with etoposide and results in decreased DNA damage after treatment. We show that BRD4 inhibitors reduce the expression of SatIII, restoring etoposide sensitivity.
CRIS-Team Scopus Importer:2023-03-21

Preclinical studies reveal that LSD1 inhibition results in tumor growth arrest in lung adenocarcinoma independently of driver mutations - Macheleidt, Iris F.; Dalvi, Priya S.; Lim, So-Young; Meemboor, Sonja; Meder, Lydia; Kaesgen, Olivia; Mueller, Marion; Kleemann, Karolin; Wang, Lingyu; Nuernberg, Peter; Ruesseler, Vanessa; Schaefer, Stephan C.; et al. (Molecular Oncology, 2018)
Lung adenocarcinoma (LUAD) is the most prevalent subtype of non-small cell lung cancer. Despite the development of novel targeted and immune therapies, the 5-year survival rate is still only 21%, indicating the need for more efficient treatment regimens. Lysine-specific demethylase 1 (LSD1) is an epigenetic eraser that modifies histone 3 methylation status, and is highly overexpressed in LUAD. Using representative human cell culture systems and two autochthonous transgenic mouse models, we investigated inhibition of LSD1 as a novel therapeutic option for treating LUAD. The reversible LSD1 inhibitor HCI-2509 significantly reduced cell growth with an IC50 of 0.3–5 μmin vitro, which was linked to an enhancement of histone 3 lysine methylation. Most importantly, growth arrest, as well as inhibition of the invasion capacities, was independent of the underlying driver mutations. Subsequent expression profiling revealed that the cell cycle and replication machinery were prominently affected after LSD1 inhibition. In addition, our data provide evidence that LSD1 blockade significantly interferes with EGFR downstream signaling. Finally, our in vitro results were confirmed by preclinical therapeutic approaches, including the use of two autochthonous transgenic LUAD mouse models driven by either EGFR or KRAS mutations. Importantly, LSD1 inhibition resulted in significantly lower tumor formation and a strong reduction in tumor progression, which were independent of the underlying mutational background of the mouse models. Hence, our findings provide substantial evidence indicating that tumor growth of LUAD can be markedly decreased by HCI-2509 treatment, suggesting its use as a single agent maintenance therapy or combined therapeutical application in novel concerted drug approaches.
CRIS-Team Scopus Importer:2023-03-21
Keywords: epigenetic alterations; HCI-2509; histone methylation; KDM1A; LSD1; lung adenocarcinoma

Pretreatment Vitamin D deficiency is associated with impaired progression-free and overall survival in hodgkin lymphoma - Borchmann, Sven; Cirillo, Melita; Goergen, Helen; Meder, Lydia; Sasse, Stephanie; Kreissl, Stefanie; Broeckelmann, Paul Jan; Von Tresckow, Bastian; Fuchs, Michael; Ullrich, Roland Tillmann; Engert, Andreas (Journal of Clinical Oncology, 2019)
PURPOSE Vitamin D deficiency is described as a modifiable risk factor for the incidence of and mortality in many common cancers; however, data in Hodgkin lymphoma (HL) are lacking. PATIENTS AND METHODS We thus performed a study measuring pretreatment Vitamin D levels in prospectively treated patients with HL and correlated this with clinical outcomes. A total of 351 patients from the German Hodgkin Study Group clinical trials (HD7, HD8, and HD9) were included. RESULTS Fifty percent of patients were Vitamin D deficient (, 30 nmol/L) before planned chemotherapy. Pretreatment Vitamin D deficiency was more common in relapsed/refractory patients than matched relapse-free controls (median baseline Vitamin D, 21.4 nmol/L v 35.5 nmol/L; proportion with Vitamin D deficiency, 68% v 41%; P <.001). Vitamin D-deficient patients had impaired progression-free survival (10-year difference, 17.6%; 95% CI, 6.9% to 28.4%; hazard ratio, 2.13; 95% CI, 1.84 to 2.48; P<001) and overall survival (10-year difference, 11.1%; 95% CI, 2.1% to 20.2%; hazard ratio, 1.82; 95% CI, 1.53 to 2.15; P <.001), consistent across trials and treatment groups. We demonstrated that Vitamin D status is an independent predictor of outcome and hypothesized that Vitamin D status might be important for the chemosensitivity of HL. We subsequently performed experiments supplementing physiologic doses of Vitamin D (calcitriol) to cultured HL cell lines and demonstrated increased antiproliferative effects in combination with chemotherapy. In an HLxenograft animal model, we showed that supplemental Vitamin D (dietary supplement, cholecalciferol) improves the chemosensitivity of tumors by reducing the rate of tumor growth compared with Vitamin D or chemotherapy alone. CONCLUSION On the basis of our clinical and preclinical findings, we encourage that Vitamin D screening and replacement be incorporated into future randomized clinical trials to properly clarify the role of Vitamin D replacement therapy in HL.
CRIS-Team Scopus Importer:2023-03-21

SQSTM1/p62 promotes miR-198 loading into extracellular vesicles and its autophagy-related secretion - Yu, Xiaojie; Eischeid-Scholz, Hannah; Meder, Lydia; Kondylis, Vangelis; Buettner, Reinhard; Odenthal, Margarete (Human Cell, 2022)
MicroRNA dysregulation is a hallmark of hepatocellular carcinoma (HCC), leading to tumor growth and metastasis. Previous screening on patient specimens identified miR-198 as the most downregulated miRNA in HCC. Here, we show that miR-198 compensation leads to self-release into extracellular vesicles (EVs). Importantly, the vesicular secretion is mediated by autophagy-related pathway, initiated by sequestration of p62/miR-198 complexes in autophagosome-associated vesicle fractions. miR-198 is selectively recognized and loaded by p62 into autophagosomal fractions, whereas mutated miR-198 forms neither induce autophagy and nor interact with p62. Gain and loss of function experiments, using a CRIPR/Cas knockout (KO) and transgenic site-specific p62 mutants, identified p62 as an essential repressor of cellular miR-198 abundancy. Notably, EVs, harboring miR-198/p62 protein complexes, can be uptaken by cells in the close vicinity, leading to change of gene expression in recipient cells. In conclusion, miR-198 enhances autophagy; conversely autophagic protein p62 reduces the miR-198 levels by sorting into extracellular space. Graphical abstract: [Figure not available: see fulltext.] miR-198 is at first transcribed as primary miRNA, after being processed into single stranded mature miR-198 form, it is transported into cytoplasm ①. By interaction with p62 protein, miR-198 conglomerates and forms a binding complex ②. Since LC3 protein is an interaction partner of p62 protein, hence miR-198 is included into autophagosomes ③. By fusion with multivesicular bodies (MVB), miR-198-binding complex was recruited into amphisomes ④, the latter of which quickly turns into secretory MVB containing intraluminal vesicles⑤. By fusion with cell membrane, intraluminal vesicles were released into extracellular space as EVs ⑥.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Autophagy; EV; HCC; microRNA; SQSTM1

Synergistic anti-angiogenic treatment effects by dual FGFR1 and VEGFR1 inhibition in FGFR1-amplified breast cancer - Golfmann, Kristina; Meder, Lydia; Koker, Mirjam; Volz, Caroline; Borchmann, Sven; Tharun, Lars; Dietlein, Felix; Malchers, Florian; Florin, Alexandra; Buettner, Reinhard; Rosen, Neal; Rodrik-Outmezguine, Vanessa; et al. (Oncogene, 2018)
FGFR1 amplification has been found in 15% of patients with breast cancer and has been postulated as a promising marker to predict response against FGFR inhibitors. However, early phase clinical trials of selective FGFR inhibitors demonstrated only limited efficacy in FGFR1-amplified breast cancer patients. We found that BGJ398, an FGFR inhibitor, effectively inhibited phosphorylation of FGFR1 and MEK/ERK signaling in FGFR1-amplified breast cancer without affecting tumor cell proliferation. However, FGFR1 knockout inhibited tumor angiogenesis in vivo. We unraveled that FGFR1 regulates the secretion of the proangiogenic vascular endothelial growth factor (VEGF) in a MAPK-dependent manner. We further found that FGF-FGFR1 signaling induces an autocrine activation of VEGF-VEGFR1 pathway that again amplifies VEGF secretion via VEGF-VEGFR1-AKT signaling. Targeting both VEGFR1 and FGFR1 resulted in synergistic anti-angiogenic treatment effects in vivo. We thus postulate synergistic treatment effects in FGFR1/VEGFR1-positive breast cancer patients by dual targeting of FGFR and VEGFR.
CRIS-Team Scopus Importer:2023-03-21

Targeted expression of mutated ALK induces neuroblastoma in transgenic mice - Heukamp, Lukas C.; Thor, Theresa; Schramm, Alexander; De Preter, Katleen; Kumps, Candy; De Wilde, Bram; Odersky, Andrea; Peifer, Martin; Lindner, Sven; Spruessel, Annika; Pattyn, Filip; Mestdagh, Pieter; et al. (Science Translational Medicine, 2012)
Activating anaplastic lymphoma kinase (ALK) mutations were recently detected in most familial and 10% of sporadic neuroblastomas. However, the role of mutated ALK in tumorigenesis remains elusive. We demonstrate that targeted expression of the most frequent and aggressive variant, ALK F1174L, is tumorigenic in mice. Tumors resembled human neuroblastomas in morphology, metastasis pattern, gene expression, and the presence of neurosecretory vesicles as well as synaptic structures. This ALK-driven neuroblastoma mouse model precisely recapitulated the genetic spectrum of the disease. Chromosomal aberrations were syntenic to those in human neuroblastoma, including 17q gain and MYCN oncogene amplification. Targeted ALK F1174L and MYCN coexpression revealed a strong synergism in inducing neuroblastoma with minimal chromosomal aberrations, suggesting that fewer secondary hits are required for tumor induction if both oncoproteins are targeted. Treatment of ALK F1174L transgenic mice with the ALK inhibitor TAE-684 induced complete tumor regression, indicating that tumor cells were addicted to ALK F1174L activity. We conclude that an activating mutation within the ALK kinase domain is sufficient to induce neuroblastoma development, and ALK inhibitors show promise for treating human neuroblastomas harboring ALK mutations.
CRIS-Team Scopus Importer:2023-03-21

Targeted next-generation sequencing for TP53, RAS, BRAF, ALK and NF1 mutations in anaplastic thyroid cancer - Latteyer, Soeren; Tiedje, Vera; Koenig, Katharina; Ting, Saskia; Heukamp, Lukas C.; Meder, Lydia; Schmid, Kurt Werner; Fuehrer, Dagmar; Moeller, Lars Christian (Endocrine, 2016)
Anaplastic thyroid carcinoma (ATC) is the most aggressive thyroid cancer with a median survival of 4–6 months. Identification of mutations contributing to aberrant activation of signaling cascades in ATC may provide novel opportunities for targeted therapy. Thirty-nine ATC samples were studied by next-generation sequencing (NGS) with an established gene panel. High quality readout was obtained in 30/39 ATC. Twenty-eight ATC harbored a mutation in at least one of the studied genes: TP53 (18/30), NF1 (11/30), ALK (6/30), NRAS (4/30), ATRX (3/30), BRAF (2/30), HRAS (2/30), KRAS (1/30). In 17/30 ATC (54 %) mutations were found in two or more genes. Twenty-one of the identified variants are listed in COSMIC as somatic mutations reported in other cancer entities. In three ATC samples no mutations were detected and none of the ATCs was positive for BRAFV600E. The most frequent mutations were found in TP53 (60 %), followed by NF1 (37 %). ALK mutations were detected in 20 % of ATC and were more frequent than RAS or BRAF mutations. ATRX mutations were identified in 10 % of the ATC samples. These sequencing data from 30 ATC samples demonstrate the accumulation of genetic alterations in ATC because in 90 % of samples mutations were already found in the investigated nine genes alone. Mutations were found with high prevalence in established tumor suppressor and oncogenes in ATC, such as TP53 and H/K/NRAS, but also, although less frequent, in genes that may harbor the potential for targeted treatment in a subset of ATC patients, such as ALK and NF1.
CRIS-Team Scopus Importer:2023-03-21
Keywords: ALK; Anaplastic thyroid cancer; ATC; ATRX; BRAF; Next-generation sequencing; NF1; RAS

Tripartite antigen-agnostic combination immunotherapy cures established poorly immunogenic tumors - Borchmann, Sven; Selenz, Carolin; Lohmann, Mia; Ludwig, Hanna; Gassa, Asmae; Braegelmann, Johannes; Lohneis, Philipp; Meder, Lydia; Mattlener, Julia; Breid, Sara; Nill, Marieke; Fassunke, Jana; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Single-agent immunotherapy has shown remarkable efficacy in selected cancer entities and individual patients. However, most patients fail to respond. This is likely due to diverse immunosuppressive mechanisms acting in a concerted way to suppress the host anti-tumor immune response. Combination immunotherapy approaches that are effective in such poorly immunogenic tumors mostly rely on precise knowledge of antigenic determinants on tumor cells. Creating an antigen-agnostic combination immunotherapy that is effective in poorly immunogenic tumors for which an antigenic determinant is not known is a major challenge. Methods We use multiple cell line and poorly immunogenic syngeneic, autochthonous, and autologous mouse models to evaluate the efficacy of a novel combination immunotherapy named tripartite immunotherapy (TRI-IT). To elucidate TRI-ITs mechanism of action we use immune cell depletions and comprehensive tumor and immune infiltrate characterization by flow cytometry, RNA sequencing and diverse functional assays. Results We show that combined adoptive cellular therapy (ACT) with lymphokine-activated killer cells, cytokine-induced killer cells, V 39Vδ 2-T-cells ( 3δ -T-cells) and T-cells enriched for tumor recognition (CTLs) display synergistic antitumor effects, which are further enhanced by cotreatment with anti-PD1 antibodies. Most strikingly, the full TRI-IT protocol, a combination of this ACT with anti-PD1 antibodies, local immunotherapy of agonists against toll-like receptor 3, 7 and 9 and pre-ACT lymphodepletion, eradicates and induces durable anti-tumor immunity in a variety of poorly immunogenic syngeneic, autochthonous, as well as autologous humanized patient-derived models. Mechanistically, we show that TRI-IT coactivates adaptive cellular and humoral, as well as innate antitumor immune responses to mediate its antitumor effect without inducing off-target toxicity. Conclusions Overall, TRI-IT is a novel, highly effective, antigen-agnostic, non-toxic combination immunotherapy. In this study, comprehensive insights into its preclinical efficacy, even in poorly immunogenic tumors, and mode of action are given, so that translation into clinical trials is the next step.
CRIS-Team Scopus Importer:2023-03-21
Keywords: immunotherapy; lung neoplasms; melanoma; sarcoma

Trophoblast Cell Surface Antigen 2 (TROP2) as a Predictive Bio-Marker for the Therapeutic Efficacy of Sacituzumab Govitecan in Adenocarcinoma of the Esophagus - Hoppe, Sascha; Meder, Lydia; Gebauer, Florian; Ullrich, Roland T.; Zander, Thomas; Hillmer, Axel M.; Buettner, Reinhard; Plum, Patrick; Puppe, Julian; Malter, Wolfram; Quaas, Alexander (Cancers, 2022)
Introduction: The Trophoblast cell surface antigen 2 (TROP2) is expressed in many carcinomas and may represent a target for treatment. Sacituzumab govitecan (SG) is a TROP2–directed antibody-drug conjugate (ADC). Nearly nothing is known about the biological effectiveness of SG in esophageal adenocarcinoma (EAC). Material and Methods: We determined the TROP2 expression in nearly 600 human EAC. In addition, we used the EAC cell lines (ESO-26, OACM5.1C, and FLO-1) and a xenograft mouse model to investigate this relationship. Results: Of 598 human EACs analyzed, 88% showed varying degrees of TROP2 positivity. High TROP2 positive ESO-26 and low TROP2 positive OACM5.1C showed high sensitivity to SG in contrast to negative FLO-1. In vivo, the ESO-26 tumor shows a significantly better response to SG than the TROP2-negative FLO-1 tumor. ESO-26 vital tumor cells show similar TROP2 expression on all carcinoma cells as before therapy initiation, FLO-1 is persistently negative. Discussion: Our data suggest that sacituzumab govitecan is a new therapy option in esophageal adenocarcinoma and the TROP2 expression in irinotecan-naïve EAC correlates with the extent of treatment response by sacituzumab govitecan. TROP2 is emerging as a predictive biomarker in completely TROP2-negative tumors. This should be considered in future clinical trials.
CRIS-Team Scopus Importer:2023-03-21
Keywords: esophageal adenocarcinoma; sacituzumab govitecan; therapy response; TROP2

Tumor vegf:vegfr2 autocrine feed-forward loop triggers angiogenesis in lung cancer - Chatterjee, Sampurna; Heukamp, Lukas C.; Sioba, Maike; Schoettle, Jakob; Wieczorek, Caroline; Peifer, Martin; Frasca, Davide; Koker, Mirjam; Koenig, Katharina; Meder, Lydia; Rauh, Daniel; Buettner, Reinhard; et al. (Journal of Clinical Investigation, 2013)
The molecular mechanisms that control the balance between antiangiogenic and proangiogenic factors and initiate the angiogenic switch in tumors remain poorly defined. By combining chemical genetics with multimodal imaging, we have identified an autocrine feed-forward loop in tumor cells in which tumor-derived VEGF stimulates VEGF production via VEGFR2-dependent activation of mTOR, substantially amplifying the initial proangiogenic signal. Disruption of this feed-forward loop by chemical perturbation or knockdown of VEGFR2 in tumor cells dramatically inhibited production of VEGF in vitro and in vivo. This disruption was sufficient to prevent tumor growth in vivo. In patients with lung cancer, we found that this VEGF:VEGFR2 feed-forward loop was active, as the level of VEGF/VEGFR2 binding in tumor cells was highly correlated to tumor angiogenesis. We further demonstrated that inhibition of tumor cell VEGFR2 induces feedback activation of the IRS/MAPK signaling cascade. Most strikingly, combined pharmacological inhibition of VEGFR2 (ZD6474) and MEK (PD0325901) in tumor cells resulted in dramatic tumor shrinkage, whereas monotherapy only modestly slowed tumor growth. Thus, a tumor cell-autonomous VEGF:VEGFR2 feed-forward loop provides signal amplification required for the establishment of fully angiogenic tumors in lung cancer. Interrupting this feed-forward loop switches tumor cells from an angiogenic to a proliferative phenotype that sensitizes tumor cells to MAPK inhibition.
CRIS-Team Scopus Importer:2023-03-21